(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
An electro-hydraulic elevator is a new type of enhanced elevators used in low-rise buildings, no more than eight floors. In this paper, an electro-hydraulic servo system for controlling the speed of a hydraulic elevator prototype by using a proportional valve and PI controller has been investigated theoretically and experimentally. A three floors elevator prototype model with 76cm height has been built, including hydraulic components and electrical components. The elevator system is automated using an Arduino UNO board based Data Acquisition (DAQ) system. LabVIEW software is programmed to control the hydraulic elevator system through L298 DC drive via the DAQ board. The best PI gains have been calculated experimentally using Ziegler–Nichols, trial and error methods. The results showed the effectiveness of the use of Electro-hydraulic servomechanism in enhancing the performance of the hydraulic elevator in terms of comfort and smoothness when people travelled through the elevator floors.